CHARACTERIZATION AND MECHANICAL PROPERTIES OF CONCRETE MIXTURES MADE WITH SEDIMENTARY LIME AND INDUSTRIAL INCINERATOR ASH (Malaysian Journal of Civil Engineering, 2018)
This paper is a review of the research work done in order to promote industrial waste into concrete for common use in building construction, with the aim of emphasizing the feasibility of use incinerator ash (IA) as fine aggregate replacement and sedimentary lime (SL) as normal cement substantial have been investigated and compared with control samples. IA were used to replace 5%, 10%,15% up to 80% of the total mineral fine aggregate’s volume and SL was used to replace 10%, 15% up to 50% of the total normal cement volume in concrete. The mixtures tests included compressive strength, tensile strength, modulus of elasticity, chloride penetration and drying shrinkage. The fresh concrete mixtures exhibited lower unit weight and acceptable workability compared to plain concrete. It was found that at the age of 28 days, the compressive strengths of concrete mixtures to decrease below the plain mixtures. In F50L25 mixtures a good mechanical properties were achieved after 28 days of curing. Given the experimental data show new possibilities for this waste materials reuse as structural concrete and give great advantages in waste minimization as well as resources conservation and reduce the cost of materials.